2017
DOI: 10.1007/s41030-017-0038-2
|View full text |Cite|
|
Sign up to set email alerts
|

Inhaler Operability and Patient Satisfaction Regarding Genuair® and Respimat® Inhalers for Chronic Obstructive Pulmonary Disease: A Randomized Crossover Study

Abstract: Introduction: Tiotropium via the Respimat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…The prevalence of overall device use errors with SMIs was computed based on the reported proportion of patients who made at least one device use error during the inhalation process. For studies that did not provide an overall error rate, [41][42][43] it was inferred based on the reported inhalation step with the highest frequency of error. For one study, 44 the overall device use error was considered the same as the reported error rate from the single inhalation step for which data were provided.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of overall device use errors with SMIs was computed based on the reported proportion of patients who made at least one device use error during the inhalation process. For studies that did not provide an overall error rate, [41][42][43] it was inferred based on the reported inhalation step with the highest frequency of error. For one study, 44 the overall device use error was considered the same as the reported error rate from the single inhalation step for which data were provided.…”
Section: Discussionmentioning
confidence: 99%
“…21 Regardless of device type, mishandling has been associated with poor health outcomes, more frequent exacerbations, increase in hospitalizations, and higher health resource utilization. [21][22][23] Thus, the economic 41 , Molimard et al 22 , Liang et al 48 , and Ding et al 39 . The rest of studies were Ngo et al 46 , Bournival et al 47 , de Oliveira et al 40 , Windisch et al 45 , Takaku et al 49 , Chorao et al 42 , and Asakura et al 43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,[26][27][28] However, these errors can be addressed through proper training and demonstration. [29][30][31][32] Common device-handling errors include 4,26,27,32,33 :…”
Section: Importance Of Proper Inhaler Techniquementioning
confidence: 99%